Tingkat Aktivitas Fisik Berhubungan dengan Tekanan Darah Pekerja di Rumah Selama Masa Pandemi COVID-19 - Ni Made Wedri; Komang Ayu Windayanti; IGA Ari Rasdini (Jurnal Gema Keperawatan, 2021)
Hypertension or high blood pressure is a condition in which a person experiences an increase in blood pressure above normal where the systolic pressure reaches 140 mmHg and the diastolic pressure reaches 90 mmHg. One of the factors that influence hypertension is physical activity. Physical activity can be done at home, at work, at school and can do activities to fill spare time. Lack of physical activity can increase the risk of suffering from hypertension. This study aims to determine the relationship of physical activity levels with blood pressure in workers who working from home during the Covid-19 pandemic. The research method was correlation analytics with cross sectional approach. The research sample numbered 68 people using sampling  probability sampling technique. Data was collected by instruments IPAQ questionnaires and blood pressure measurements using sphygmomanometer. The results showed that most respondents had moderate physical activity in 31 people (45.6%) and blood pressure of respondents in the normal category of 26 people (38.2%). The test results used  spearman rank with a value of 0.004 α (0.05) and a value of r = -0.348 The correlation is negative, which means that the higher the level of physical activity, the lower the blood pressure. It can be concluded that there is a relationship between the level of physical activity and blood pressure in workers who work from home during the Covid-19 pandemic in the Seririt Village area in 2021.